Depression and quality of life in older adults on hemodialysis - de Alencar, Saulo B.V. (Braz J Psychiatry, 2019)
OBJECTIVE: Depression is highly prevalent in hemodialysis patients, but few studies have evaluated older hemodialysis patients. The aim of this study was to evaluate the prevalence of depression, its associated factors and its impact on quality of life in an older population on hemodialysis. METHODS: This was a cross-sectional study including 173 hemodialysis patients aged 60 years or older in Recife, Brazil. Depression was evaluated using the Mini-International Neuropsychiatric Interview when depressive symptoms (according to the 5-item Geriatric Depression Scale) were present. Quality of life was assessed with the Control, Autonomy, Self-realization and Pleasure Questionnaire (CASP-16). Data were also collected on sociodemographic, laboratory (albumin, parathormone, hemoglobin, and phosphorus) and dialysis (dialysis vintage, vascular access and hemodialysis adequacy) characteristics. RESULTS: Depression was present in 22.5% of the sample. Depressed patients presented low CASP-16 quality of life scores (31.6 vs. 24.2, p < 0.001), twice the odds of albumin levels < 3.8 g/dL (OR 2.36; 95%CI 1.10-5.07; p = 0.027) and higher parathormone levels (OR 1.06; 95%CI 1.00-1.13; p = 0.05). CONCLUSION: Older hemodialysis patients have a high prevalence of depression. Depressed patients presented poor quality of life, lower serum albumin and higher parathormone levels. Teams dealing with older hemodialysis patients should include depression and quality of life assessments in care protocols.